Verbalization of nominalizations: A typological commentary on the article by Nikki van de Pol. (May 2019) - Malchukov, Andrej
Abstract: The present article provides a typological commentary on the article by Nikki van de Pol (2019) on the history of the English gerund. It is shown that in spite of certain idiosyncratic aspects, the history of the verbal gerund illustrates a well-known grammaticalization path of verbalization, whereby deverbal nouns are first grammaticalized into nonfinite forms (participles, infinitives, converbs), and may later be integrated into the verbal paradigm. It is further suggested that the mixed behavior attested for the verbal gerund, which deviates both from the nominal and from the clausal prototype, may be universally supported by constructional polysemy and blending with constructions which have further progressed on the verbalization cline. Highlights: Provides typological perspective on the history of the English verbal gerund. Demonstrates that verbalization is a common typological grammaticalization path. Discusses universal constraints on category-mixing in gerund nominalizations. Admits construction blending as a general factor in verbalization scenarios.